Impact of Early Screening for Gestational Diabetes on Perinatal Outcomes in High-Risk Women - Hong, Winston Y.; Biggio, Joseph R.; Tita, Alan; Harper, Lorie M. (American Journal of Perinatology, 2016)
Objective To examine the benefits of early gestational diabetes mellitus (GDM) screening in a high-risk population.Study Design Retrospective cohort of all singletons diagnosed with GDM with indications for early screening: GDM or macrosomia in a prior pregnancy or obesity. Subjects were classified as early (<20 weeks) or routine (>24 weeks) screening. Patients diagnosed with GDM were managed according to standard institutional protocols. Outcomes examined were cesarean delivery (CD), preeclampsia, large for gestational age (LGA), small for gestational age (SGA), macrosomia, and preterm birth (PTB).Results Subjects screened early were more likely to have had GDM in a prior pregnancy, hypertension, higher body mass index, and higher fasting glucose. Early and routine screening groups had similar incidences of CD (adjusted odds ratio [AOR] 0.95, 95% confidence interval [CI] 0.55–1.64), preeclampsia (AOR 0.84, 95% CI 0.38–1.83), LGA (AOR 0.90, 95% CI 0.51–1.72), SGA (AOR 0.38, 95% CI 0.13–1.13), and macrosomia (AOR 1.00, 95% CI 0.53–1.87). Subjects in the early screening group had a higher incidence of PTB (AOR 1.79, 95% CI 1.08–2.99).Conclusion We did not detect a benefit to early screening for women who met the criteria. The utility of early GDM screening requires evaluation in a prospective trial.
Keywords: gestational diabetes; insulin; early screening